The evolutionary dynamics of major regulators for sexual development among Hymenoptera species - Biewer, Matthias; Schlesinger, Francisca; Hasselmann, Martin (Frontiers in Genetics, 2015)
All hymenopteran species, such as bees, wasps and ants, are characterized by the common principle of haplodiploid sex determination in which haploid males arise from unfertilized eggs and females from fertilized eggs. The underlying molecular mechanism has been studied in detail in the western honey bee Apis mellifera, in which the gene complementary sex determiner (csd) acts as primary signal of the sex determining pathway, initiating female development by csd-heterozygotes. Csd arose from gene duplication of the feminizer (fem) gene, a transformer (tra) ortholog, and mediates in conjunction with transformer2 (tra2) sex-specific splicing of fem. Comparative molecular analyses identified fem/tra and its downstream target doublesex (dsx) as conserved unit within the sex determining pathway of holometabolous insects. In this study, we aim to examine evolutionary differences among these key regulators. Our main hypothesis is that sex determining key regulators in Hymenoptera species show signs of coevolution within single phylogenetic lineages. We take advantage of several newly sequenced genomes of bee species to test this hypothesis using bioinformatic approaches. We found evidences that duplications of fem are restricted to certain bee lineages and notable amino acid differences of tra2 between Apis and non-Apis species propose structural changes in Tra2 protein affecting co-regulatory function on target genes. These findings may help to gain deeper insights into the ancestral mode of hymenopteran sex determination and support the common view of the remarkable evolutionary flexibility in this regulatory pathway.